The effect of semantic transparency on the processing of morphologically derived words: Evidence from decision latencies and event-related potentials. - Jared, Debra; Jouravlev, Olessia; Joanisse, Marc F. (Journal of Experimental Psychology. Learning, Memory & Cognition, 2017)
Decomposition theories of morphological processing in visual word recognition posit an early morpho-orthographic parser that is blind to semantic information, whereas parallel distributed processing (PDP) theories assume that the transparency of orthographic-semantic relationships influences processing from the beginning. To test these alternatives, the performance of participants on transparent (foolish), quasi-transparent (bookish), opaque (vanish), and orthographic control words (bucket) was examined in a series of 5 experiments. In Experiments 1-3 variants of a masked priming lexical-decision task were used; Experiment 4 used a masked priming semantic decision task, and Experiment 5 used a single-word (nonpriming) semantic decision task with a color-boundary manipulation. In addition to the behavioral data, event-related potential (ERP) data were collected in Experiments 1, 2, 4, and 5. Across all experiments, we observed a graded effect of semantic transparency in behavioral and ERP data, with the largest effect for semantically transparent words, the next largest for quasi-transparent words, and the smallest for opaque words. The results are discussed in terms of decomposition versus PDP approaches to morphological processing.